The Fascination of Sociology - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
This article is an overview of the behavioral science of sociology, stressing its weaknesses in terms of lack of preciseness and limitations on some occasions as well as its strengths in other circumstances, which could be so lucrative that they may even arouse abusing intentions. On the other hand, sociology shares such interesting traits with other close social sciences and even has something common with art and even natural sciences. Nevertheless it is a formal discipline unattainable for the layman and is indeed a fascinating field to explore and its study contributes societies on the way to improvements. (C) 2015 Published by Elsevier Ltd.
Keywords: Sociology; society; behavior; social science